UJI AKTIVITAS ANTIOKSIDAN ISOLAT FUNGI ENDOFIT DAUN GALING-GALING (Cayratia trifolia L.) DENGAN METODE 1,1-DIPHENYL-2-PICRYLHYDRAZIL (DPPH) - Magfirah Abdullah; Fitriana Fitriana; St. Maryam (Fakultas Farmasi UMI, 2020)
Endophytic fungi generally produce secondary metabolites that have beneficial biological activities such as anticancer, antiviral, antibacterial or antioxidant compounds. The aim of this study was to examine the antioxidant activity of galling-galing leaf endophytic fungi isolate (Cayratia trifolia L.) by 1,1-diphenyl-2-picrylhydrazil (DPPH) method. This study used IDGG-03 endophytic fungi isolate fermented for 21 days using MYB medium then extracted and evaporation was carried out. The fermentate extract obtained was then tested qualitatively and quantitatively for antioxidant activity. Qualitative results using TLC plates indicate that galling-leaf fungi isolates have antioxidant activity which is characterized by the presence of yellow spots on a purple background. And in the quantitative test IC50 68,133 µg / mL was obtained, which indicated the antioxidant activity of galling-vane leaf endophytic fungi isolate (Cayratia trifolia L.) classified as a strong antioxidant.